Mononuclear Silver Complexes for Efficient Solution and Vacuum‐Processed OLEDs. Issue 24 (23rd October 2018) - Romanov, Alexander S.; Jones, Saul T. E.; Yang, Le; Conaghan, Patrick J.; Di, Dawei; Linnolahti, Mikko; Credgington, Dan; Bochmann, Manfred
Abstract: Carbene metal amides are a new class of highly efficient light‐emitting molecules based on a linear donor–metal–acceptor geometry. Here the synthesis, structure, and photo‐ and electroluminescence of carbene silver carbazolato complexes, ( Ad L)Ag(Cz) [ Ad L = adamantyl‐substituted cyclic (alkyl)(amino)carbene; Cz = carbazolate (1 ) and 3, 6‐ t Bu2 Cz (2 )], are reported. They display green emission with photoluminescence quantum yields of up to 74%. Efficient mixing of triplet and singlet excited states is observed, with sub‐microsecond thermally activated radiative triplet lifetimes. These complexes provide prototype organic light‐emitting diodes based exclusively on silver emitters, with external quantum efficiencies of up to 14%. Abstract : Carbene‐metal‐amides based on silver allow organic light‐emitting diode (OLED) fabrication by both solution and thermal vapor deposition techniques. Rotational flexibility leads to a thermally activated delayed fluorescence type process with very low activation energy and sub‐microsecond triplet harvesting. These are the first OLEDs based solely on silver.